1992
DOI: 10.1001/jama.1992.03480150043029
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentives for Organ Donation: The Perspectives of Health Care Professionals

Abstract: Physician Fraud and Medicaid Physician Fraud and Medicaid Physician Fraud and MedicaidTo the Editor. \p=m-\Thearticle "Fraud by Physicians Against Medicaid" by Jesilow et al1 is seriously misleading. Its main conclusion, appearing in the abstract, is that "sanctioned physicians show an overrepresentation of psychiatrists, foreign medical graduates, and minority group physicians." The text of the article does not substantiate this conclusion. The authors do not, in fact, provide additional information other tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The refusal to provide consent continues to be a major barrier in procuring organs. 14,18,70,[108][109][110] Although multiple surveys of both the general public 1,111 and health care professionals 71,72,112,113 have shown a willingness to donate organs, these results may not predict actual consent rates. 1,70,114 Hospital characteristics, 110,115 the timing of the request, 14,109,115 the background of the requester, 72,116,117 and the demographic characteristics of potential donors and their families 118-120 may influence consent rates.…”
Section: Obtaining Consentmentioning
confidence: 99%
“…The refusal to provide consent continues to be a major barrier in procuring organs. 14,18,70,[108][109][110] Although multiple surveys of both the general public 1,111 and health care professionals 71,72,112,113 have shown a willingness to donate organs, these results may not predict actual consent rates. 1,70,114 Hospital characteristics, 110,115 the timing of the request, 14,109,115 the background of the requester, 72,116,117 and the demographic characteristics of potential donors and their families 118-120 may influence consent rates.…”
Section: Obtaining Consentmentioning
confidence: 99%
“…Surveyed health professionals in transplantation have suggested previously that providing incentives to the family or potential donor may increase the number of potential donors (20,27) and found similar support for financial incentives similar to those studied here (28). The lack of acceptability of certain financial incentives, notably monetary payment, by health professionals may stem from their comfort level in discussing donation with families once financial incentives are offered (33) or their perceived "moral inappropriateness" of offering cash (20). Further, it is interesting to note that whereas a tax credit is akin to monetary payment in terms of value in this survey, there were notable differences in preferences for the two forms of financial incentives across the different groups.…”
Section: Discussionmentioning
confidence: 53%
“…Third, although the findings of studies 20,34,35 in this area are somewhat mixed, support for financial incentives among at least some healthcare professionals seems to be increasing over time. For example, in 1987, Altshuler and Evanisko 20 found that 10%, 16%, and 8% of neurosurgeons, organ procurement coordinators, and critical-care nurses, respectively, supported offering incentives to donor families.…”
Section: Discussionmentioning
confidence: 99%
“…20 -26 Empiric evidence to support either of these opposing positions, however, is scant. Few studies have examined the attitudes of either the public 10,11,[27][28][29][30][31][32][33] or healthcare professionals 20,34,35 toward incentives for organ donation. These studies typically focus on the general category "financial incentives" rather than on specific incentives and thus their results are difficult to interpret.…”
mentioning
confidence: 99%